High performance of the linked visible photoinitiator for free radical polymerization based on erythrosine B derivative. Issue 31 (9th May 2015) - Nan, Xuying; Huang, Yi; Fan, Qinguo; Shao, Jianzhong
ABSTRACT A novel erythrosine B derivative linked with a tertiary amine used as a visible light initiator for free radical polymerization was synthesized and characterized. For comparison, the free hydrophobic erythrosine B derivative was also synthesized and its combination with the tertiary amine was used as the separated two component photoinitiator. The linked initiator exhibited higher photoinitiator efficiency in high viscosity monomer than in low viscosity one, compared with the separated counterpart. Especially, when it was combined with iodonium salt, the further promotion of the photoinitiator efficiency was observed, compared with the separated three component system. It was found that as iodonium salt together with tertiary amine was continuously added to the formula with the linked initiator, the photoinitiator efficiency was dramatically enhanced compared with the same addition to the formula with the separated counterpart, revealing the application potential of the linked initiator. And the continuous addition of either the iodium salt or the tertiary amine to the formula only leaded to the small size increase of the photoinitiator efficiency. These results suggested that there existed an interdependent relationship between iodonium salt and tertiary amine in promoting the photoinitiator efficiency of the dye/amine/iodonium salt system. For these, the corresponding synergistic mechanism was proposed. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42361.